2020
DOI: 10.1016/j.cognition.2020.104239
|View full text |Cite
|
Sign up to set email alerts
|

The value of choice facilitates subsequent memory across development

Abstract: Both children and adults are more likely to remember information when they have control over their learning environment. Despite many demonstrations of this effect in the literature, it is still unclear how and why people are more likely to remember information that is obtained through their own actions rather than passively received. One possibility is that individuals are biased to remember the outcomes of their choices because doing so may often be beneficial. Having agency, or the ability to exert control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
3
16
1
Order By: Relevance
“…Traditional empirical work in procedural learning has focused on actions only; the absence of a significant interaction between agency and RPE in the current study indicates that participants use RPEs to learn about both states and their own actions while performing a declarative learning task (see also Rouhani et al, 2018;Rouhani et al, 2020). Surprisingly, in contrast to the current and earlier studies where a mere effect of agency was found (DuBrow et al, 2019;Murty et al, 2015;Rotem-Turchinski et al, 2019), Katzman and Hartley (2020) argued that agency itself is not sufficient to enhance memory. In their experiment, participants performed a memory task where the utility of agency (i.e., the degree to which participants' choices were rewarded Fig.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Traditional empirical work in procedural learning has focused on actions only; the absence of a significant interaction between agency and RPE in the current study indicates that participants use RPEs to learn about both states and their own actions while performing a declarative learning task (see also Rouhani et al, 2018;Rouhani et al, 2020). Surprisingly, in contrast to the current and earlier studies where a mere effect of agency was found (DuBrow et al, 2019;Murty et al, 2015;Rotem-Turchinski et al, 2019), Katzman and Hartley (2020) argued that agency itself is not sufficient to enhance memory. In their experiment, participants performed a memory task where the utility of agency (i.e., the degree to which participants' choices were rewarded Fig.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, even being able to choose the order and the timing of item presentation, has been associated with increased memorization in both adult (Markant et al, 2016) and child (Ruggeri et al, 2019) learners. Overall, evidence suggests that being in control of one's own learning experience by having the opportunity to choose is critical for successful declarative learning (but see Katzman & Hartley, 2020, and the Discussion section).…”
mentioning
confidence: 99%
“…In one such study, adolescents demonstrated greater reward-based modulation of hippocampal-striatal connectivity than adults, and the strength of this connectivity predicted reward-related memory ( Davidow et al, 2016 ). However, other studies have not found evidence for developmental change in the influence of valenced outcomes on memory ( Cohen et al, 2019a ; Katzman and Hartley, 2020 ). The influence of different motivational and reward signals on memory across development may not be straightforward — individual and developmental differences in neurocognitive processes including sensitivity to valenced feedback ( Ngo et al, 2019 ; Rosenbaum et al, 2020 ), curiosity ( Fandakova and Gruber, 2021 ), and emotional processing ( Adelman and Estes, 2013 ; Eich and Castel, 2016 ) may interact, leading to complex relations between age, motivation, and memory performance.…”
Section: Discussionmentioning
confidence: 84%
“…This rewarding nature of controllable experience creates an intrinsic motivation to discover controllable events, which has been proposed to be a key driver of development (Heckhausen, 2011) and can serve as an effective objective function enabling artificial agents to develop complex action repertoires (Klyubin et al, 2005;Salge et al, 2014). Like explicit rewards, control facilitates learning and memory (Chambon et al, 2020;Cockburn et al, 2014), even from a young age (Katzman & Hartley, 2020;Ruggeri et al, 2019). Collectively, these findings suggest that inferences of environmental controllability play a key role in the development of an individual's behavioral repertoire and their acquisition of foundational knowledge about the structure of one's environment.…”
mentioning
confidence: 99%